Transformative learning: integrating extended reality into outcome-based education in higher education - Mohamed Sofiadin, Aidrina (HRMARS, 2025)
Outcome-based education (OBE) represents a paradigm shift in educational practices, emphasizing the achievements and competencies learners should demonstrate upon completion of a learning experience. By inherently aligning the educational system with specific learning outcomes, OBE enables educators to personalize and adapt instruction to meet diverse student needs. The integration of Extended Reality (XR) technologies—encompassing Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR)— presents an innovative avenue to enhance learning experiences within this framework. Through systematic literature approach, this paper explores the principles underpinning OBE, the challenges inherent in its implementation alongside XR technologies, and the transformative outcomes in higher education. This paper aimed to help instructors to understand how they can embrace OBE into practical action by integrating XR. This could guide the instructors in their course planning, including teaching and assessment planning. This paper does not attempt to be a complete guide on OBE, rather it introduces some initiatives on how XR technology could support OBE. single lines pacing. The incorporation of Extended Reality within an Outcome-Based Education framework has the potential to revolutionize learning experiences in higher education. By explaining the principles of OBE, addressing implementation challenges, and recognizing the transformative outcomes of this integration, educators can create immersive learning environments that not only cater to diverse learners but also prepare them for real-world challenges.